Physical Education Teachers in Educational Units: To What Extent Do They Contribute to Swimm Sports Achievement in Schools? - Mashud Mashud; Muhammad Amin Priambudi; Recky Ahmad Haffyandi (Universitas Sriwijaya, 2024)
The aim of this research is to determine the extent of the role and contribution of Physical Education teachers to sports achievements in schools. Sports achievements in this research are focused on sports which is one of the sports contested in the National Student Sports Olympiad. The method used is a qualitative research method. The data collection technique uses interview techniques focusing on understanding a phenomenon through interaction. Reflexive thematic analysis data analysis techniques consist of; 1) recognizing data, 2) generating codes, 3) developing themes, 4) reviewing potential themes, 5) defining and naming themes, and 6) creating a report. The research correspondents consisted of class V and VI athletes who excelled in the National Student Sports Olympiads at the South Kalimantan Province level and sports practitioners, namely parents and accompanying teachers, in this case, Physical Education teachers. The results of the data analysis articulate that the role of Physical Education teachers in developing swimming performance is not yet visible, in fact, it is very minimal. Students practice swimming because they join clubs at the direction of their parents or family.